Perancangan Fasilitas Sleeping Box di area Tunggu Bandara Juanda – Terminal 2 - Stephanie Sugianto; mariana wibowo (Intra, 2015)
Sleeping Box facilities in Wait Around Juanda Airport - Terminal 2 is designed to meet the needs of passengers who were waiting for hours when experiencing flight delay flight and transit. These facilities include all the necessities needed while waiting for passengers, among other amenities lying, sitting facilities, working facilities, entertainment facilities, and storage facilities. The concept used in this design is "Serenity", a word that describes a very comfortable situation, and supported with modern minimalist style. Interior design and furniture design made as comfortable and complete as possible so that passengers can feel comfortable despite being in a state of waiting. Results are presented in interior design Sleeping Box is a comfortable atmosphere as well as full facilities so that passengers who are waiting can enjoy their waiting time with something better.